From “aged care” to “smart elderly care”. A corpus-based jurilinguistics analysis in Chinese and English - Guo, Weiwei; Veleanu, Corina (Comparative Legilinguistics, 2024)
The concept of “care” is complex and multifaceted, and it is evolving rapidly in our digitized societies. By comparing the contexts of occurrence of the term in English and Chinese, this research aims to shed light on its evolution and diverse interpretations across cultures and legal systems. The development of technology has led to a growing digital divide, which can be addressed through a human rights-based approach, a business-based approach, or a combination of both. In China, the term “smart elderly care” has emerged to address the growing demand for technology-driven care solutions, while in the English-speaking world, the term “aged care” has gained prominence. The European Union has invested in programs and strategies to promote the use of digital technologies in elder care, introducing new concepts such as “older persons in long-term care” and “Older Persons’ LTC”. A linguistic analysis of English and Chinese legal corpora has revealed the diachronic evolution of the term “care” from psychological care to technical gestures and attitudes involving digital technologies. In Chinese, the term “care” is expressed differently depending on the context, words used, and participants involved in the speech acts. This research underscores the importance of understanding the complexity of the term “care” and its diverse interpretations across cultures and legal systems. By bridging the gap between these different perspectives, we can develop more effective and inclusive approaches to elder care in an increasingly digitalized world.